2021
DOI: 10.1103/physrevb.104.094428
|View full text |Cite
|
Sign up to set email alerts
|

MoP3SiO11 : A 4d3 honeycomb antiferromagnet with disconnected octahedra

Abstract: We report the crystal structure and magnetic behavior of the 4d 3 spin-3/2 silicophosphate MoP 3 SiO 11 studied by high-resolution synchrotron x-ray diffraction, neutron diffraction, thermodynamic measurements, and ab initio band-structure calculations. Our data revise the crystallographic symmetry of this compound and establish its rhombohedral space group (R 3c) along with the geometrically perfect honeycomb lattice of the Mo 3+ ions residing in disconnected MoO 6 octahedra. Long-range antiferromagnetic orde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Since we have used both SOC and trigonal distortion smaller than Hund's coupling, this theory is more applicable to 3d 3 than 5d 3 systems, where J eff = 3/2 may be a better starting point than S=3/2 spin states. Recent works [37][38][39] of 5d 3 have shown that in these systems there is a large spin gap. We propose that this may be relevant to the atomic SOC discussed in this work.…”
Section: Contributions From Anion Socmentioning
confidence: 99%
“…Since we have used both SOC and trigonal distortion smaller than Hund's coupling, this theory is more applicable to 3d 3 than 5d 3 systems, where J eff = 3/2 may be a better starting point than S=3/2 spin states. Recent works [37][38][39] of 5d 3 have shown that in these systems there is a large spin gap. We propose that this may be relevant to the atomic SOC discussed in this work.…”
Section: Contributions From Anion Socmentioning
confidence: 99%